La pittura può evocare il sublime kantiano? (Lebenswelt. Aesthetics and philosophy of experience., 2024)
Can painting evoke an experience of the sublime, understood in the terms adopted by Kant in the Critique of the Power of Judgment? I will present three considerations that imply that painting cannot evoke the Kantian sublime. I will then point out some problems related to each consideration. I will explain how some paintings can evoke an experience of the sublime, even when painting is understood in terms of the eighteenth-century European context. In this way, I intend to show the real possibility of the Kantian sublime as a reaction to pictorial art.